(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The development of mobile banking in developing countries has prompted an increasing number of studies on the factors influencing its adoption. However, research findings are still scattered across various theoretical models and contexts, resulting in a lack of a comprehensive synthesis of dominant themes, development trends, and future research directions. This study aims to analyze the development of mobile banking adoption studies in developing countries through a Systematic Literature Review (SLR) and bibliometric analysis. The study used the PRISMA 2020 guidelines for Scopus-indexed journal articles published between 2022 and 2025. Inclusion criteria included English-language articles discussing mobile banking adoption in developing countries, while proceedings, book chapters, duplicate articles, and irrelevant publications were excluded from the analysis. Of the 147 identified articles, 58 met the criteria and were analyzed using VOSviewer. The results showed that dominant themes included the Technology Acceptance Model (TAM), UTAUT, trust, risk perception, customer satisfaction, and adoption behavior. The analysis also identified a shift towards financial inclusion, fintech integration, digital transformation, service quality, and customer loyalty. These findings provide a current synthesis of mobile banking research developments and serve as a basis for developing a research agenda on digital financial ecosystems in developing countries.